2013
DOI: 10.1007/s00213-013-3217-3
|View full text |Cite
|
Sign up to set email alerts
|

Is the rodent maternal separation model a valid and effective model for studies on the early-life impact on ethanol consumption?

Abstract: RationaleEarly-life events can cause long-term neurobiological and behavioural changes with a resultant effect upon reward and addiction processes that enhance risk to develop alcohol use disorders. Maternal separation (MS) is used to study the mediating mechanisms of early-life influences in rodents. In MS studies, the pups are exposed to maternal absence during the first postnatal weeks. The outcome of MS experiments exhibits considerable variation and questions have been raised about the validity of MS mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
108
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(117 citation statements)
references
References 123 publications
(230 reference statements)
6
108
0
2
Order By: Relevance
“…Using the modified intermittent access paradigm with three consecutive days of access to 20% alcohol for seven weeks, the median alcohol intake during the last week of access in all alcohol-drinking animals was 3.2 g/kg (1.8-5.8 g/kg) and the preference was 36.4% (16.0-46.2%). This is in agreement with previous studies using intermittent access paradigms in which alcohol consumption up to 6 g/kg has been described [22,[29][30][31][32] and higher compared to studies in which Wistar rats were given continuous alcohol access [20,31,33]. Moreover, compared to our recent study [16] in which the animals had intermittent access to 20% alcohol on Mondays, Wednesdays and Fridays the modified model used herein resulted in a higher alcohol intake and a higher preference as well as an increased intake and preference over time.…”
Section: Alcohol Intake Using Three Consecutive Days Of Intermittent supporting
confidence: 93%
“…Using the modified intermittent access paradigm with three consecutive days of access to 20% alcohol for seven weeks, the median alcohol intake during the last week of access in all alcohol-drinking animals was 3.2 g/kg (1.8-5.8 g/kg) and the preference was 36.4% (16.0-46.2%). This is in agreement with previous studies using intermittent access paradigms in which alcohol consumption up to 6 g/kg has been described [22,[29][30][31][32] and higher compared to studies in which Wistar rats were given continuous alcohol access [20,31,33]. Moreover, compared to our recent study [16] in which the animals had intermittent access to 20% alcohol on Mondays, Wednesdays and Fridays the modified model used herein resulted in a higher alcohol intake and a higher preference as well as an increased intake and preference over time.…”
Section: Alcohol Intake Using Three Consecutive Days Of Intermittent supporting
confidence: 93%
“…It should be noted that this involved extensive handling and repeated IP injections over a three week period during adolescence. It has been well documented that various manipulations to rodents during the early-life period can have profound effects on hedonic behaviour in adulthood (Flagel et al, 2003;Kosten et al, 2000Kosten et al, , 2005Kosten et al, , 2006Lynch et al, 2005;Martini and Valverde, 2012;Matthews et al, 1999;Moffett et al, 2006Moffett et al, , 2007Nylander and Roman, 2013;Silveira et al, 2010;Yajie et al, 2005), as such, we conducted a separate experiment where maternally-separated animals were injected with vehicle alone, while another group of maternallyseparated animals received no injections during the adolescent period. We found the maternal-separation induced reduction in cocaine-taking remained intact independent of whether the animals had received adolescent handling and injections or had not (presented as area under the curve for reasons of succinctness).…”
Section: Discussionmentioning
confidence: 99%
“…Because the HPA axis is frequently dysregulated in physical and psychiatric illnesses (Andersen and Teicher, 2009;Baumeister et al, 2014;Teicher and Samson, 2013), and its altered function has been reported as a vulnerability condition for the development of psychopathology phenotypes, such as depressive and anxiety phenotypes (Andersen, 2015;Cirulli et al, 2003;Franklin et al, 2012;Pryce and Feldon, 2003), Consequently, there is a special interest in preclinical studies in developing and validating naturalistic models that are able to approximate human ELS conditions (Molet et al, 2014;Nylander and Roman, 2013;Schmidt et al, 2011;Vetulani, 2013). However, for animals the repertoire of early life conditions is more restricted, making comparisons with humans difficult (Heim and Nemeroff, 2002;Teicher et al, 2006).…”
Section: Introductionmentioning
confidence: 98%
“…Although maternal separation is the ELS model most often used to replicate early adversities, other paradigms with briefer or longer periods of separation have also been investigated (for an overview of all postnatal separation models, see Gutman and Nemeroff, 2002;Heim and Nemeroff, 2002;Pryce and Feldon, 2003;Veenema, 2009). 5 The major effect of the significant increase in postnatal separation models in the literature is evident in the heterogeneity of definitions and methodological procedures adopted by such studies (Anisman et al, 1998;Molet et al, 2014;Nishi et al, 2014;Nylander and Roman, 2013;Schmidt et al, 2011;Vetulani, 2013). Consensus on defining the steps to be followed by postnatal separation models is lacking.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation